2023
DOI: 10.3847/1538-4357/ad0dfe
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Steady Sub-Alfvénic Solar Wind in Comparison with Super-Alfvénic Wind from Parker Solar Probe Measurements

Yiming Jiao,
Ying D. Liu,
Hao Ran
et al.

Abstract: We identify more than 10 steady sub-Alfvénic solar wind intervals from the measurements of the Parker Solar Probe (PSP) from encounter 8 to encounter 14. An analysis of these sub-Alfvénic intervals reveals similar properties and similar origins. In situ measurements show that these intervals feature a decreased radial Alfvén Mach number resulting from a reduced density and a relatively low velocity, and that switchbacks are suppressed in these intervals. Magnetic source tracing indicates that these sub-Alfvéni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…They find that the location of the Alfvén surface for these flows varies between 15 and 24 R e , which is larger than the canonical value of 11-12 R e typically assumed for fast solar wind originating from an open coronal hole. Jiao et al (2024) find that the sub-Alfvénic intervals observed so far all exhibit similar properties and origins.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…They find that the location of the Alfvén surface for these flows varies between 15 and 24 R e , which is larger than the canonical value of 11-12 R e typically assumed for fast solar wind originating from an open coronal hole. Jiao et al (2024) find that the sub-Alfvénic intervals observed so far all exhibit similar properties and origins.…”
Section: Introductionsupporting
confidence: 57%
“…The first entry of the NASA Parker Solar Probe (PSP) spacecraft into a sub-Alfvénic solar wind flow lasted for 5 hr on 2021 April 28 and has been studied extensively since then (Kasper et al 2021;Alberti et al 2022;Bandyopadhyay et al 2022;Zank et al 2022;Zhang et al 2022;Zhao et al 2022b;Liu et al 2023;Jiao et al 2024). Unlike the super-Alfvénic solar wind, the turbulence properties of this new solar wind environment are connected magnetically to the surface of the Sun.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of electron density as a representation of the plasma density may introduce an overestimate of the local Alfvén speed by 2%-5% (Mostafavi et al 2022). We use PSP data from encounters 8-10 and encounters 12-13, during which sub-Alfvénic solar wind measurements are reported (Jiao et al 2024). We exclude encounter 11 due to the absence of the QTN density for this encounter.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Because of the enhanced Alfvén radius of an LMBL, PSP made the first glimpse of the sub-Alfvénic plasma for about 5 hr around a heliocentric distance of about 19 solar radii at the eighth encounter on 2021 April 28 (Kasper et al 2021). Now, more than 10 steady sub-Alfvénic intervals can be identified from PSP measurements since encounter 8, and a statistical analysis of these intervals confirms their nature as LMBLs (Jiao et al 2024). Inside the corona, the sonic critical point, at which the solar wind changes from subsonic to supersonic, is usually thought to be well below the Alfvén critical point, i.e., at a few solar radii (Matthaeus 2021, and references therein).…”
Section: Introductionmentioning
confidence: 84%